2022
DOI: 10.3389/fimmu.2022.1021102
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Sequencing approach for exploring the therapeutic effect of umbilical cord mesenchymal stem/stromal cells on lipopolysaccharide-induced acute lung injury

Abstract: Acute lung injury (ALI) is significantly associated with morbidity and mortality in patients with critical diseases. In recent years, studies have identified that mesenchymal stem/stromal cells (MSCs) ameliorate ALI and pulmonary fibrosis. However, the mechanism underlying this outcome in ALI has not yet been investigated. In this study, RNA sequencing technology was used to analyze the gene expression profile of lung tissue in lipopolysaccharide (LPS)-induced ALI rats following treatment with human umbilical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Having clarified the improved effects of MSC spheroids‐EXO on LPS‐induced ALI mice, we were curious about the differences at the molecular level. RNA‐seq analyses of the lung tissues harvested from 4 groups of mice were performed according to a standard process, as we previously reported 12 . As shown in Figure 3A, the principal component analysis of messenger RNA (mRNA) expression data shows the alternated properties of different groups: A: Control group (age‐sex matched healthy mice with no intervention), B: ALI + PBS treatment group, C: ALI + MSC‐EXO treatment group, D: ALI + MSC spheroids‐EXO treatment group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Having clarified the improved effects of MSC spheroids‐EXO on LPS‐induced ALI mice, we were curious about the differences at the molecular level. RNA‐seq analyses of the lung tissues harvested from 4 groups of mice were performed according to a standard process, as we previously reported 12 . As shown in Figure 3A, the principal component analysis of messenger RNA (mRNA) expression data shows the alternated properties of different groups: A: Control group (age‐sex matched healthy mice with no intervention), B: ALI + PBS treatment group, C: ALI + MSC‐EXO treatment group, D: ALI + MSC spheroids‐EXO treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq analyses of the lung tissues harvested from 4 groups of mice were performed according to a standard process, as we previously reported. 12 As shown in Figure 3A, the principal component analysis of messenger RNA (mRNA) expression data shows the alternated properties of different groups: A: Control group (age-sex matched healthy mice with no intervention), B: ALI + PBS treatment group, C: ALI + MSC-EXO treatment group, D: ALI + MSC spheroids-EXO treatment group. Heatmap analysis indicated relatively tidy correlation coefficients among the samples in the same group (Figure 3B).…”
Section: Transcriptomic Profiles and Differential Expression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…16 MSCs are not brandnew therapy in the treatments of pulmonary diseases. Previous studies have demonstrated that patients with chronic obstructive pulmonary disease, 16 ARDS 17 or pulmonary fibrosis 18,19 could benefit from MSCbased therapy which reduces the inflammation and pulmonary tissue damage, improves the respiratory function, pulmonary microenvironment and reduces the mortality. At the same time, the anti-infammatory and immunomodulatory characteristics of MSC-based therapy make them as ideal candidates for the treatment of patients with acute and chronic inflammatory lung diseases.…”
Section: Introductionmentioning
confidence: 99%